Challenging muscle homeostasis uncovers novel chaperone interactions in Caenorhabditis elegans - Frumkin, Anna; Dror, Shiran; Pokrzywa, Wojciech; Bar-Lavan, Yael; Karady, Ido; Hoppe, Thorsten; Ben-Zvi, Anat (Frontiers in Molecular Biosciences, 2014)
Proteome stability is central to cellular function and the lifespan of an organism. This is apparent in muscle cells, where incorrect folding and assembly of the sarcomere contributes to disease and aging. Apart from the myosin-assembly factor UNC-45, the complete network of chaperones involved in assembly and maintenance of muscle tissue is currently unknown. To identify additional factors required for sarcomere quality control, we performed genetic screens based on suppressed or synthetic motility defects in Caenorhabditis elegans. In addition to ethyl methyl sulfonate-based mutagenesis, we employed RNAi-mediated knockdown of candidate chaperones in unc-45 temperature-sensitive mutants and screened for impaired movement at permissive conditions. This approach confirmed the cooperation between UNC-45 and Hsp90. Moreover, the screens identified three novel co-chaperones, CeHop (STI-1), CeAha1 (C01G10.8) and Cep23 (ZC395.10), required for muscle integrity. The specific identification of Hsp90 and Hsp90 co-chaperones highlights the physiological role of Hsp90 in myosin folding. Our work thus provides a clear example of how a combination of mild perturbations to the proteostasis network can uncover specific quality control modules.